PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN MONOPOLI PADA TEMA “PERKEMBANGAN TEKNOLOGI” UNTUK SISWA KELAS III SDN 2 PRINGGABAYA UTARA - Renata Utami Mahardika; Muhammad Turmuzi; Khairun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop media math educational games for grade IVelementary school students and test its feasibility and effectiveness in improvingunderstanding of the concept of fractions. The background of this research is thelow interest of students in learning and difficulty in understanding the material, sothat interactive and fun media is needed. The method used is Research andDevelopment (R&D) with the ADDIE model which consists of Analysis, Design,Development, Implementation, and Evaluation stages. The research subjectsinvolved material experts, media experts, class teachers, and students. Theresults of material expert validation obtained a score of 98.6% in the “veryfeasible” category, while media expert validation reached 90% in the “veryfeasible” category. Phase I small group test resulted in 85% (category “veryinteresting”), while phase II increased to 96.7% (category “very interesting”). Theresults of implementation showed that the educational game media was able toincrease learning motivation, student involvement, and better understanding offraction concepts. Thus, the educational game media developed is declared veryfeasible and effective for use in learning mathematics elementary schools, and canbe an alternative learning innovation to create a more meaningful and enjoyablelearning atmosphere.